A facile preparation of temperature-stable borate ultra-low permittivity microwave ceramics for LTCC applications. Issue 11 (1st August 2020) - Xi, Juan; Shang, Fei; Liu, Fei; Xu, Jiwen; Chen, Guohua
Abstract: An ultra-low permittivity Li2 O-added CuO-ZnO-B2 O3 multiphase ceramic was fabricated by means of sintering technique, and the phase compositions, microstructures and dielectric properties were investigated. Specimens can be sintered below 800 °C. All the sintered samples consist of Zn(BO2 )2 and CuB2 O4 . The variations in the microstructure and dielectric properties of borate ceramics samples were relied on the sintering temperature. The ceramic sintered at 785 °C for 2 h exhibits excellent dielectric properties of ϵr  = 2.86, Q ×  f  = 38093 GHz (~16.0 GHz), τƒ  = -2.17 ppm/°C, which indicates that the ceramic is a promising candidate for LTCC applications.